RES diffusion and R&D investments in the flexibilisation of the European electricity networks. (March 2016) - Corsatea, Teodora Diana; Giaccaria, Sergio; Covrig, Catalin-Felix; Zaccarelli, Nicola; Ardelean, Mircea
Abstract: The present analysis adds up to the discussion carried around the flexibilisation of the electricity networks, as means of higher diffusion of renewable energy sources (RES). Inspiring from innovation studies the paper proposes an economic rationale for considering RES technology manufacturers as investors in electricity networks. Moreover, the present analysis scrutinize the extent to which the various economic operators within specific segments of the power supply chain invest in a portfolio of research and development activities, among which the electricity grids and storage technologies. The intensity of these research investments was mapped across the European countries for the year of 2011. Their geographic distribution confirms the rationale of an analysis based on canonical correlation testing the associations between RES market diffusion and power network indicators. The analysis provides useful insights for specific technology, such as the one revealing PV market sensitivity to research investments in storage technologies, confirming a potential business model coupling the two technologies. Accommodating this pattern and enabling further diversification of research portfolios, the public incentives could be redesigned in order to address the flexibilisation of power networks.